Mathematical methods for solving problems of electrodynamics in a layered environment. Issue 1 (October 2021) - Kogay, G D; Tyo, A L; Drozd, V G; Ten, T L; Omarova, S E; Ivanov, V L; Ayazhanov, K S
Abstract: The article considers methods for solving applied problems of electrodynamics in the case of layered and vertically inhomogeneous environments. This article suggests the algorithms of primary processing of GPR data. GPR data at a fixed observation point are investigated via the "selecting" method. The analysis of the frequency response of the signal energy distribution by frequency components is being processed. We proposed software implementation for determining the depth of objects and the relative dielectric permittivity of the subsurface environment. To perform this task, we use a module to determine the depth and conductivity of subsurface objects. The computational part was performed by the computationally common method of the approximate solution. As a result of the research, we have developed numerical methods for solving direct electrodynamics problems.